Variation in phosphorus supply alters nitrogen metabolism in the nodules and roots of Virgilia divaricata, a Cape fynbos indigenous legume from the Cape Floristic Region - Magadlela, Anathi (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.